PERBANDINGAN METODE AHP DAN SAW DALAM MENENTUKAN CALON KARYAWAN - Kevin Kevin; Bagus Mulyawan; Novario Jaya Perdana (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
During this time in selecting prospective employees, still using manual methods. Therefore the solution needed is to make an application for selecting candidates using the AHP and SAW methods. This application can facilitate the company in selecting prospective employees. Data collection techniques used were observation and interviews. In working on this application using several structured methods such as flowcharts, context diagrams, and relationships between tables. The programming language used in designing this application is PHP and uses the MySQL database. The method used to perform calculations on this application is the AHP and SAW methods. The results of the comparison of the AHP and SAW methods have differences because, the calculation stages between the two methods are different. In determining the criteria weights in the AHP method are determined by comparing the values between criteria, while the SAW method has determined the weight of the criteria With the creation of this website-based employee candidate selection application, it is expected to help the company in determining prospective employees.